Adrenal crisis mainly manifested as recurrent syncope secondary to tislelizumab: a case report and literature review - Wei, Haishan; Zuo, Anju; Chen, Jiying; Zheng, Chunyan; Li, Tingting; Yu, Haiyan; Guo, Yuan (Frontiers in Immunology, 2024)
As an immune checkpoint inhibitor (ICI), tislelizumab is an anti-programmed cell death protein 1 (PD-1) drug. With the extensive application of ICIs, there is an ever-increasing proportion of immune-related adverse events (irAEs) in clinical settings, some of which may even be life-threatening. Herein, we present a patient with tislelizumab-induced adrenal crisis. The main clinical manifestation was recurrent syncope accompanied by high-grade fever. Timely identification and hormone replacement therapy helped the patient overcome the crisis well. Finally, the patient discontinued tislelizumab and switched to antibody–drug conjugate (ADC) therapy. We report this case to improve our understanding of this situation, identify this kind of disease, and prevent adrenal crisis in time. Eventually, limiting toxicities reduces the interruption of immunotherapy. Since irAEs are multisystem damage with more non-specific symptoms, except for oncologists, general practitioners who endorse the need for taking a holistic approach to the patient should play a vital role in the management of cancer treatment.